THE STABILIZATION MODEL OF SUPPLY AND RAW MATERIAL PRICE FOR CARRAGEENAN INDUSTRY - MARYAM SETYADEWI (NIM : 234 100 52); Pembimbing : Dr. Andi Cakravastia Raja, ST. MT., NOOR
One of the problems faced in the development of seaweed industrial structure were instability supply and price of dried seaweed as raw materials for processing industries. This is caused by dried seaweed supply from collectors for the domestic market is less than exported. This leads the availability of dried seaweed in the domestic market limited and expensive. Government intervention can be used as a solution to the stabilization of supply and market prices. This research aims to develop a model of the structure of the seaweed industry that represents government intervention in an attempt to meet the availability of supply of dried seaweed in domestic market and provide stability of raw material prices in the industry as well as stability of carrageenan price on the consumer. Entities in the seaweed industry system under study consists of farmers, collectors, BLURI, carrageenan industry, carrageenan consumers and government. Government policy instruments proposed as a form of intervention in the form of export tax policy determination to the collectors, export quotas, price support programs to farmers and industrial development incentives in the form of value added tax exemption on the sold carrageenan products. This research produces a model draft of seaweed industrial structure as the mathematical models with the objective function to maximize the total profit for each of the entities involved in the system. Stages of the research that have been conducted consists of three main stages, namely (1) the identification of problems and analysis phase of the system, (2) the model development stage which includes determining of the initial model system and a model of the system design that consists of three schemes of government intervention scenario, (3) the verification stage, system validation and analysis of results. The test models results show that model system design able to solve the problems of supply and price instability of raw materials in the dried seaweed industry level as well as the sale price of carrageenan on the consumer level as indicated by the decrease in the number of imported raw materials accompanied by increased profits in carrageenan industry and decreased cost of carrageenan on consumer purchasing .